Optimalisasi pembelajaran ilmu pengetahuan sosialmelalui strategi peta konsep untuk meningkatkan Aktivitas belajar siswa kelas VII A SMP N 3 Polokarto tahun ajaran 2015/2016 - Wulandari, Destyana Ayu, Drs. Djumali, M.Pd (2016)
The purpose of this research is to increase the activity of students in social studies learning by using concept map strategies in class VII A SMP N 3 POLOKARTO. This research is a classroom action research (CAR) using qualitative descriptive analysis, namely the development of students how to analyze data from the first cycle to the second cycle. The subjects were students of class VII A SMP N 3 POLOKARTO totaling 32 students. Subject implementing measures is Social Science teachers, assisted by investigators. Data were collected by using observation, field notes, documentation and interviews. Data analysis technique used is descriptive qualitative consisting of data reduction, data presentation and conclusion. The results of this study showed an increase in students' learning activities through a strategy map concept. It can be seen from: 1) Students who ask questions before the action of 18.75% and amounted to 78.12% after the action, 2) Students who answered questions from other students and a teacher before action by 15.62% and after the action is 75%, 3) Students who advise prior to action by 21.88% and amounted to 81.25% after the action, 4) Students who express an opinion before the action amounted to 28.12% and amounted to 84.37% after the action. Based on research data of the class action can be concluded that through a strategic concept maps can enhance students' learning activities.